The Prevalence and Cost Implications of Bloodstream Infection Producing Extended-Spectrum Beta-Lactamase (ESBL) in Adult Patients at Dr. Soetomo General Academic Hospital - Kurniati, Neneng Dewi; Syahrir, Irwan; Musa Ghufron (Universitas Muhammadiyah Surabaya, 2025)
Bloodstream infections (BSIs) caused by extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae represent a growing concern in healthcare settings, particularly in tertiary hospitals. These infections are associated with limited therapeutic options, increased mortality, and rising healthcare costs. This study aimed to describe the clinical, microbiological, and economic characteristics of adult inpatients diagnosed with hospital-acquired (HA) BSIs due to ESBL-producing Enterobacteriaceae at Dr. Soetomo General Academic Hospital from January 1 to December 31, 2024. A cross-sectional study was conducted using retrospective data from adult inpatients (≥18 years) with confirmed HA-BSIs caused by ESBL-producing Escherichia coli, Klebsiella pneumoniae, or Proteus mirabilis. Only the first positive blood culture per patient was analyzed. Community-acquired infections and non-Enterobacteriaceae organisms were excluded. The most frequent pathogen was Escherichia coli ESBL, especially among patients from medical wards. BSIs occurred predominantly in medical and intensive care units. Notably, microbiological confirmation of ESBL-producing organisms led to higher claim reimbursements through the national health insurance system, yielding a positive cost margin despite longer hospital stays and expensive treatment regimens. In conclusion, ESBL-producing Enterobacteriaceae remain a major challenge in managing HA-BSIs at Dr. Soetomo General Academic Hospital. While clinically burdensome, accurate microbiological diagnosis also supports optimal resource utilization and insurance claim efficiency in the hospital setting.